Long-term efficacy, safety, and patient-reported outcomes of apitegromab in patients with spinal muscular atrophy: results from the 36-month TOPAZ study - Crawford, Thomas O.; Day, John W.; De Vivo, Darryl C.; Krueger, Jena M.; Mercuri, Eugenio; Nascimento, Andres; Pasternak, Amy; Mazzone, Elena Stacy; Duong, Tina; Song, Guochen; Marantz, Jing L.; Baver, Scott; et al. (Frontiers in Neurology, 2024)
Background and purpose At 12 months in the phase 2 TOPAZ study, treatment with apitegromab was associated with both an improved motor function in patients with Type 2 or 3 spinal muscular atrophy (SMA) and with a favorable safety profile. This manuscript reports the extended efficacy and safety in the nonambulatory group of the TOPAZ study at 36 months. Methods Patients who completed the primary study (NCT03921528) could enroll in an open-label extension, during which patients received apitegromab 20 mg/kg by intravenous infusion every 4 weeks. Patients were assessed periodically via the Hammersmith Functional Motor Scale–Expanded (HFMSE), Revised Upper Limb Module (RULM), World Health Organization (WHO) motor development milestones, Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) Daily Activities and Mobility domains, and Patient-Reported Outcomes Measurement Information System (PROMIS) Fatigue questionnaire. Results Of the 58 patients enrolled in TOPAZ, 35 were nonambulatory (mean age 7.3 years). The mean change at 36 months in HFMSE score from baseline was +4.0 (standard deviation [SD]: 7.54), and + 2.4 (3.24) for RULM score (excluding n = 7 after scoliosis surgery). Caregiver-reported outcomes (PEDI-CAT and PROMIS Fatigue) showed improvements from baseline over 36 months. In addition, most patients (28/32) improved or maintained WHO motor milestones achieved at baseline. The most frequently reported treatment-emergent adverse events were pyrexia (48.6%), nasopharyngitis (45.7%), COVID-19 infection (40.0%), vomiting (40.0%), and upper respiratory tract infection (31.4%). Conclusion The benefit of apitegromab treatment observed at 12 months was sustained at 36 months with no new safety findings.